PEMANFAATAN TANAMAN PARASIT TALI PUTRI (CASSYTHA FILIFORMIS L.)SEBAGAI MOLLUSCASIDA KEONG MAS (POMACEA CANALICULATA LAMARCK) - Nur Hidayah dan Essy Purwaningtyas (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
This research aims to know the use of saponin substance contained in the extract of tali putri,Cassytha filiformis L., as the molluscicide material to the cold‐blooded animal, golden snail, as thedestructive pests of young rice plant.The subject of this research was molluscicide and the object was the extract of tali putri. Theresearcher tested whether the content of saponin in the extract of this plant could be made as a naturalmolluscicide. Afterwards, it was carried out an experiment to several golden snails.The results of the research shows that the content of the saponin substante in the extract of taliputri can be made as the molluscicide material for the cold‐blooded animal, golden snail. Futhermore,the experiment indicates that 100% of the examined golden snail died less than 24 hours after thetreatment.Keywords: tali putri, molluscicide, golden snail.